Prescripción del ejercicio en adultos con dolor musculoesquelético crónico - Alex Damián, Flores Bone (2020)
The purpose of this research is to identify the effects of exercise prescription in the treatment of chronic musculoskeletal pain in adult population, through the collection and analysis of scientific articles such as Pubmed, Science Direct, Google Scholar and PEDro. They record a large number of evidence-based on publications and a high impact on physical therapy treatment. Chronic pain lasts for more than three months or persists beyond the time needed for the tissues to be healed or for the latent disease to resolve. Musculoskeletal origin pain is the most common cause found in clinical consultation. This study concludes that exercise has favorable physiological effects in adults with chronic pain of musculoskeletal etiology. The type of exercise performed or the discipline practiced is not significant, as long as the parameters involved in performing the physical activity which are worked progressively; even if the pain perceives in the patient during its execution. For the selection and categorization of 192 articles, the PEDro scale, the Scimago Journal Rank and the average citation count were used. Thirty randomized clinical trials were counted with 3379 study subjects. Also, 5 articles of systematic review and meta-analysis are included during this literature review.